OBJECTIFICATION AND COMMODITY FEMINISM IN PANTENE INDONESIA ADVERTISEMENTS: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Albert Tallapessy; Ghanesya Harimurti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Advertising plays a significant role in shaping public perceptions of gender and beauty, often reinforcing dominant social ideologies through verbal and visual representations. This study investigates how women are objectified in Indonesian hair-care advertising by analyzing two Pantene commercials, The Raline Look Super Straight Hair! (2015) and For Hair, No More Half-Hearted! (2022). The study aims to examine the discursive strategies through which these advertisements construct female identity and reproduce gendered power relations within neoliberal consumer culture. This research employs Multimodal Critical Discourse Analysis (MCDA), integrating Fairclough’s three-dimensional framework of Critical Discourse Analysis, van Leeuwen’s theory of visual representation, and Nussbaum’s theory of objectification. The analysis focuses on spoken utterances, on-screen text, visual representations, and character interactions to explore the relationship between textual features, discursive practices, and broader social structures. The findings reveal that both advertisements construct women as deficient subjects whose social value depends on achieving an idealized hairstyle through product consumption. The 2015 commercial associates flawless hair with personal identity, attractiveness, and self-worth, thereby positioning women as objects of visual evaluation. Meanwhile, the 2022 commercial employs performative shaming, in which a male character attributes a woman’s romantic failure to inadequate hair care, reinforcing male authority in defining female value. Across both advertisements, objectification is normalized through narratives framed as humorous, aspirational, and empowering, obscuring the patriarchal assumptions embedded within the promotional discourse. The study concludes that Pantene’s advertising discourse reproduces and adapts patriarchal ideologies by linking female worth to physical appearance and consumer practices.